Quality, identity and practice in offshore university programmes: issues in the internationalization of Australian higher education - Chapman, A.; Pyvis, David (Routledge Publishing, Taylor & Francis Group, 2006)
This paper reports the findings of qualitative case studies aimed at exploring student experiences of offshore programmes delivered in Singapore, Hong Kong and Malaysia by Australian universities. The paper draws on a cross-case analysis of the studies to develop propositions about student experience and identity formation in the context of offshore education. The propositions are that: offshore students consider international education to be part of a long-term trajectory of identity formation, with the choice of programme delivery being a strategy to progress along the trajectory; offshore students seek identity as members of the educational community through pursuing local ways of belonging; and offshore students deal with the demands of family, work and study by prioritizing and compartmentalizing roles and activities. The findings provide insights into student perspectives on what makes a quality educational experience for international students studying offshore.